Temperature compensation for physical unclonable function (I) - Zhou, Xian (Nanyang Technological University, 2020)
Current Mirror Array Physical Unclonable Function (CMA PUF) circuit is one type of PUF that has non-linear relationship between output current and the voltage, and that non-linear relationship is used to generate challenge and response pair (CRP). CMA PUF, unlike the delay type PUF which has a linear relationship, is prone to machine learning attack. Thus, It has great potential in the security sectors in reality. However, there are problems on reliability of PUF due to the environment factor, mainly the temperature. Therefore, a temperature model is proposed in this report to deal with the environment factor. The model is derived from the subthreshold equations and able to predict the response for the PUF accurately, across a range of -45℃ - 90℃ . The simulation results show that the reliability has improved to around 98% for the worst case.